Entrepreneurial Orientation Scale: Adaptation to Spanish. (25th July 2016) - Boada-Grau, Joan; Sánchez-García, José Carlos; Viardot, Eric; Boada-Cuerva, Maria; Vigil-Colet, Andreu
Abstract: Entrepreneurship is linked to the perception of opportunities, to orientation, to attitudes, to the fear of failure and to entrepreneurial motivations. Entrepreneurial orientation is a fundamental construct for understanding the phenomenon of entrepreneurship. What is more, it is multidimensional and has attracted considerable attention from researchers in recent years. The objective of this study was to adapt the original 12-item English scale to Spanish and to analyze its psychometric properties. The participants in the present study were 925 Spanish employees (48.2% men, 51.5% women, M age = 42.49 years, SD age = 11.25) from the Autonomous Communities of Catalonia and Castilla-León. After applying an ESEM (RMSEA = .06; CFI = .97 and TLI = .95) a structure was determined made up of four factors which corroborated the structure of the original scale: Autonomy (α = .71 and CI = .68 – .73), Innovativeness (α = .70 and CI = .67 – .73), Risk Taking (α = .72 and CI = .68 – .74) and Competitive Aggressiveness (α = .70 and CI = .67 – .73). The four factors displayed suitable reliability. The study also found evidences of validity in relation to a series of external correlates and various scales which refer to workaholism, irritation and burnout. The scale presented here may prove useful for satisfactorily identifying, in Spanish, the entrepreneurial orientation of the working population.